Repercussões do uso de psicofármacos no processo de amadurecimento do psicótico - Queiroz, Raquel Carvalho de (2014)
In the current context of the treatment of psychosis, there is an emphasis in favor of use, almost exclusively, of psychotropic drugs. In this way, we have pointed out the importance of considering the impact of this abusive use in the ripening process of this subject. For both, the present research used the bibliographic data bases of the Scielo, NCBI, Fiocruz, Anvisa and WHO; in addition to online libraries of universities and psychoanalytic´s institutions. For the searches, we used descriptors such as: treatment of psychosis, ripening process of Winnicott and excessive use of psychotropic drugs. We depart from the constitution and evolution of psychiatric knowledge and psychoanalytic about insanity. Then, based on the theory of the maturation process of the subject of Winnicott, is presented the panorama of this theory, in order to substantiate that form the medication´s can interfere in this process. Finally, are discussed the proposals of psychoanalytic and psychiatric treatment of psychosis, highlighting the consequences of improper use of medicines. In this regard, the present study points to the importance for an ethical practice of professionals who works with this clinical specificity. In addition, we emphasize the fundamental aspect of cautious use of psychotropic drugs for which he may assist the subject in the resumption of the process.